Genetic attributes of Iranian cystic fibrosis patients: the diagnostic efficiency of CFTR mutations in over a decade - Hosseini Nami, Amin; Kabiri, Mahboubeh; Zafarghandi Motlagh, Fatemeh; Shirzadeh, Tina; Fakhari, Negar; Karimi, Ali; Bagherian, Hamideh; Jamali, Mojdeh; Younesikhah, Shahrzad; Shadman, Sara; Zeinali, Razie; Zeinali, Sirous (Frontiers in Genetics, 2023)
Objectives: Cystic fibrosis (CF) is the most prevalent autosomal recessive disorder among Caucasians. Mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR) cause this pathology. We, therefore, aimed to describe the CFTR mutations and their geographical distribution in Iran. Method: The mutation spectrum for 87 families from all Iranian ethnicities was collected using ARMS PCR, Sanger sequencing, and MLPA. Results: Mutations were identified in 95.8% of cases. This dataset revealed that the most frequent mutations in the Iranian population are F508del, c.1000C>T, c.1397C>G, c.1911delG, and c.1393-1G>A. Additionally, we found weak evidence for Turkey being the possible geographical pathway for introducing CFTR mutations into Iran by mapping the frequency of CFTR mutations. Conclusion: Our descriptive results will facilitate the genetic detection and prenatal diagnosis of cystic fibrosis within the Iranian population.